2013
DOI: 10.1002/jmv.23847
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine effectiveness during the 2012 influenza season in Victoria, Australia: Influences of waning immunity and vaccine match

Abstract: Vaccine effectiveness may wane with increasing time since vaccination. This analysis used the Victorian sentinel general practitioner (GP) network to estimate vaccine effectiveness for trivalent inactivated vaccines in the 2012 season. A test‐negative design was used where patients presenting to GPs with influenza‐like illness who tested positive for influenza were cases and noncases were those who tested negative. Vaccination status was recorded by GPs. Vaccine effectiveness was calculated as (1‐odds ratio) ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Similar epidemiological findings have been reported in China (Cai et al, 2014). In comparison, the subclade 3A viruses were detected at a prevalence of 13-40% in the 2011-2012 influenza seasons in Australia and European countries (Fantoni et al, 2014;Pariani et al, 2013;Sullivan et al, 2014). Although these three subclades (3A, 3B and 3C) were antigenically indistinguishable (WHO, 2012), the variety of different circulating subclades in different regions around the world suggests that a seasonal vaccine targeted at more regionally circulating seasonal viruses may provide more optimum protection for the local populations.…”
Section: Discussionsupporting
confidence: 85%
“…Similar epidemiological findings have been reported in China (Cai et al, 2014). In comparison, the subclade 3A viruses were detected at a prevalence of 13-40% in the 2011-2012 influenza seasons in Australia and European countries (Fantoni et al, 2014;Pariani et al, 2013;Sullivan et al, 2014). Although these three subclades (3A, 3B and 3C) were antigenically indistinguishable (WHO, 2012), the variety of different circulating subclades in different regions around the world suggests that a seasonal vaccine targeted at more regionally circulating seasonal viruses may provide more optimum protection for the local populations.…”
Section: Discussionsupporting
confidence: 85%
“…An Australian study reported a decline in VE, but it was sensitive to the cut-off chosen [33]. In this study we modelled time since vaccination as a spline, which provides added value to the categorical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found declines in VE for influenza A (H3N2) over time, with their VE estimates showing non-significant protection from the vaccine after several months [3][4][5][6][7] or evidence for increased infection with longer time since vaccination [14]. However, some of these studies had relatively small sample sizes and thus may have been underpowered to identify statistically significant VE even when it existed.…”
Section: Discussionmentioning
confidence: 95%
“…Yearly revaccination is necessary because circulating strains and/or vaccine composition change every influenza season. Additionally, previous studies have found that influenza vaccine effectiveness (VE) declines over time since vaccination in some populations does not provide significant protection in most cases after 90-120 days [3][4][5][6][7]. Many factors impact VE estimates and speed of decline -including age, comorbidities, herd immunity, use of adjuvants, type of vaccine administered (live attenuated or inactivated), prior natural influenza exposure, prior influenza vaccination, antigenic drift, and study design [6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 96%